mTOR-dependent upregulation of xCT blocks melanin synthesis and promotes tumorigenesis - Li, Chunjia (Cell Death Differ, 2019)
Loss of either TSC1 or TSC2 causes tuberous sclerosis complex (TSC) via activation of mTOR signaling pathway. The two prominent features of TSC are skin lesions including hypomelanic macules and benign tumors in multiple organs, whose molecular alterations are largely unknown. We report here that X(c)(−) cystine/glutamate antiporter (xCT) was elevated in Tsc2(−/−) or Pten(−/−) cells, Tsc1 knockout mouse tissues and TSC2-deficient human kidney tumor. xCT was transcriptionally boosted by mTOR-mediated Oct1 signaling cascade. Augmented xCT led to reduction of eumelanin and elevation of pheomelanin in Tsc1 skin knockout mice through mTOR signaling pathway. Disruption of xCT suppressed the proliferation and tumorigenesis of Pten-null cells and Tsc2-null cells. mTOR hyperactive cells were more sensitive to inhibitors of mTOR or xCT. Combined inhibition of mTOR and xCT synergistically blocked the propagation and oncogenesis of mTOR hyperactive cells. Therefore, oncogenic mTOR activation of xCT is a key connection between aberrant melanin synthesis and tumorigenesis. We suggest that xCT is a novel therapeutic target for TSC and other aberrant mTOR-related diseases.